اختيار الشروط المثلى لتحديد الزرنيخ في الأوساط المائية بطريقة المعايرة الكمونية (Latakia University Journal -Basic Sciences Series, 2013)
يهدف هذا البحث إلى دراسة تأثير بعض الشروط التحليلية في تحديد الزرنيخ في الأوساط المائية بطريقة المعايرة الكمونية ومن ثم اختيارها بوصفها شروطاً مثلى معتمدة لهذا التحديد. تمت دراسة تأثير كل من(قيمةPH الوسط ، نوع وتركيز المحلول الموقي ، تأثير الشوارد المعيقة) على تحديد الزرنيخ في الأوساط المائية بالمعايرة الكمونية وذلك باستخدام محلول قياسي من اليود. كما تم العمل على رفع حساسية الطريقة والوصول بحد الكشف إلى مرتبة ppm. إذ تجدر الإشارة إلى أنّ هناك شروطاً  hWتقنية يجب ضبطها لتحديد القيمة الفعلية لنقطة نهاية المعايرة ومعالجة البيانات الخاصة بسحاحة المحلول القياسي (السرعة الأولية والتباطؤ بالقرب من نقطة نهاية المعايرة). أظهرت الدراسة أن قيمة الـPH المناسبة للمعايرة الكمونية للزرنيخ باليود تترواح بين(PH:8-9)،كما تبين أن الاستجابة العملية للزرنيخ على مسرى البلاتين كانت سريعة عند استخدام Na2SO4 بوصفه محلولاً موقياً بتركيز0.1M والتي استخدمت بنجاح للتحديد الكمي للزرنيخ As3+ بحد كشف يصل إلى2×10-6 mol/l. كما تبين خلال الدراسة عدم إمكانية تحديد الزرنيخ بوجود شوارد النحاس في المحلول، في حين لا تؤثر وجود شوارد الرصاص والكبريتات والكلوريد.  This research aims to study the effect of certain analytical conditions to determine the arsenic in aqueous media using a Potentiometric, and then choose and adopt the optimum conditions for this determinism. We studied the effect of each of the (PH value, type, concentration puffer, effect of crippling electrolytes) to determine the arsenic in aqueous media and calibration using a standard solution of iodine. We also worked on raising the sensitivity of the method detection limit access to the ppm. It should be noted that technical conditions must be tuned to determine the actual value of the end point calibration and data processing of standard solution (initial velocity and deceleration near the end point calibration). The study showed that the PH value appropriate for calibration of arsenic with   iodine (8-9), also found that the response process of arsenic on the electrode platinum has been excellent when using Na2SO4 as puffer with concentration of 0.1 M, which has been successfully used to quantify arsenic As+3 up to detect up to 2 × 10-6M. As it turns out during the study, it was not possible to determine the arsenic presence of copper ions in the solution, while the presence of lead and sulfate ions and chloride was not affective.